2008
DOI: 10.1002/pssa.200879733
|View full text |Cite
|
Sign up to set email alerts
|

Transparent diamond‐on‐glass micro‐electrode arrays for ex‐vivo neuronal study

Abstract: We report on the fabrication of high aspect ratio diamond Micro Electrode Arrays (MEAs) grown on silicon as well as on glass substrates using an optimised nanoseeding technique and Bias Enhanced Nucleation (BEN). Such MEA systems combine high electrode reactivity and high electrical current injection limits with resiliency, biocompatibility and optical transparency of diamond surfaces. We present the technological steps for the fabrication of 2D as well as 3D diamond microelectrode arrays. The patterning issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…It can be applied to various substrates [97][98][99], on large surfaces, up to eight inches [100,101]. Contrary to BEN, 3D substrates like silicon tips [102,103] or silica optical fibers [104] can be homogeneously coated [105]. The main challenge is the improvement of diamond films adhesion [20,93].…”
Section: Deposition Of Ndsmentioning
confidence: 98%
“…It can be applied to various substrates [97][98][99], on large surfaces, up to eight inches [100,101]. Contrary to BEN, 3D substrates like silicon tips [102,103] or silica optical fibers [104] can be homogeneously coated [105]. The main challenge is the improvement of diamond films adhesion [20,93].…”
Section: Deposition Of Ndsmentioning
confidence: 98%
“…The diameters of electrodes are between 10 and 25 µm with a separation of 100-250 µm. Bergonzo et al [52] and Carabelli et al [53] utilized nano-crystalline diamond films to generate electrode arrays.…”
Section: Diamond Micro-and Ultramicro-electrode Arraysmentioning
confidence: 99%
“…nitrate, 4-nitrophenol [49][50][51], Cr(VI) ions, Ag(I) ions, sulphate, peroxodisulfate [43], hydrogen peroxide [55]), for bio-detections (e.g. detection of dopamine [44][45][46][47][48], neuronal activity measurements [52,53], quantal catecholamine secretion from chromaffine cells [54]), and for the generation and detection of peroxidisulfate with the aid of scanning electrochemical microscope (SECM) [59]. We have shown that dopamine can be sensitively and selectively detected on diamond ultramicroelectrode arrays in the presence of ascorbic acid [55].…”
Section: Diamond Micro-and Ultramicro-electrode Arraysmentioning
confidence: 99%
“…These arrays were contacted as a group and were used as single electrodes to improve the sensitivity while retaining the advantages of a microelectrode in a traditional macroscopic electrochemical setup. Individually addressed electrodes, for in vitro neuron studies, have been fabricated by selective seeding before diamond growth [16]. There has, however, been very little research on the development of BNCD microband array electrodes for microfluidic systems.…”
Section: Introductionmentioning
confidence: 99%